Ballerina body : dancing and eating your way to a leaner, stronger, and more graceful you - Copeland, Misty; Jones, Charisse (Grand Central Life & Style, 2017)
"The celebrated ballerina and role model, Misty Copeland, shares the secrets of how to reshape your body and achieve a lean, strong physique and glowing health,"--Amazon.com.